Which outcomes should be included in a core outcome set for capturing and measuring doctor well-being? A Delphi study - Gemma Simons; David S Baldwin; Naomi Klepacz (BMJ Open)
Objectives To develop a core outcome set (COS) to capture and measure the well-being of doctors working in the National Health Service (NHS).Design An online Delphi study.Setting UK NHS.Participants Participants from four stakeholder groups: (1) those who might use the COS in research, (2) organisations that measure/capture NHS staff well-being, (3) professionals with experience managing NHS staff well-being and (4) NHS doctors were identified through authorship of relevant publications, attendee lists of doctor well-being conferences and meetings, professional bodies, participation in a previous study and recommendations from others. They were recruited via email.Interventions A two-stage process: (1) creating a list of 43 well-being outcomes informed by a systematic review of well-being measurement instruments, a survey of UK doctors and two doctor engagement workshops and (2) an online Delphi study (with two rounds) to reach consensus. Outcomes were rated on a 9-point Likert scale; ‘consensus’ was reached when ≥75% agreed that an outcome was critical for inclusion in the COS.Results 52 participants completed both Delphi rounds. Seven well-being outcomes met the threshold for inclusion in the COS: general well-being, health, personal safety, job satisfaction, morale, life work balance and good clinical practice.Conclusions Use of the COS has the potential to reduce heterogeneity and standardise the capture and measurement of doctor well-being, and ensure outcomes important to all stakeholders are reported.Trial registration This study was prospectively registered with the Core Outcome Measures in Effectiveness Trial initiative at www.comet-initiative.org (Registration: 1577).